Synthesis of NaX Zeolite from Blitar Kaolin via Hydrothermal and Sonication Methods with Alkali Fusion Pre-treatment - Susi Nurul Khalifah; Saidun Fiddaroini; Aminatus Arifah; Awwali Maf’ulah Hasanah; Anton Prasetyo (Jurnal Kimia Sains dan Aplikasi, 2025)
NaX zeolite, widely recognized for its applications in cation exchange, adsorption, and catalysis, was successfully synthesized from Blitar natural kaolin using an alkali fusion pre-treatment, followed by two comparative synthesis methods: hydrothermal and sonication. The synthesis was conducted at 70°C for 2 and 4 hours. Optimal conditions were achieved with a NaOH/kaolin weight ratio of 2.0 and a synthesis gel composition of 10SiO2: 1Al2O3: 6Na2O: 180H2O (molar ratio). X-ray diffraction (XRD) confirmed the transformation of natural kaolin into sodium silicate, with sonication yielding phase-pure NaX zeolite, while the hydrothermal method resulted in NaX with sodalite impurities. Fourier-transform infrared (FTIR) spectroscopy identified characteristic NaX vibrations, and scanning electron microscopy (SEM) revealed cubic-shaped particles in the sonication method. The sonication process accelerated crystallization, producing higher-purity zeolite in shorter times than hydrothermal synthesis. These findings emphasize the effectiveness of sonication in enhancing the crystallinity and purity of NaX zeolite, offering a robust, time-efficient alternative for large-scale zeolite production.